2010
DOI: 10.1007/s10212-010-0044-3
|View full text |Cite
|
Sign up to set email alerts
|

Assimilation attitudes predict lower immigration-related self-efficacy among Israeli immigrant teachers

Abstract: This study focuses on self-efficacy among teachers working in culturally diverse educational contexts. We put forward the notion of immigration-related self-efficacy and provide initial support for its relationship with the acculturation attitudes held by immigrant teachers. One hundred thirty-three teachers who immigrated to Israel from the Former Soviet Union participated in this study. We found that teachers tend to report high levels of self-efficacy in all the investigated aspects. According to our predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 18 publications
4
16
1
3
Order By: Relevance
“…In accordance with previous study (Hachfeld et al, 2015;Tatar et al, 2011) and our hypothesis, immigration-related self-efficacy was predicted by attitudes toward multiculturalism, such that a pluralistic multicultural attitude to school was related to higher immigration-related self-efficacy. Attitudes toward multiculturalism were not a significant predictor of teachers' diversity-related burnout, not in accordance with our hypothesis.…”
Section: Attitudes Toward Multiculturalismsupporting
confidence: 92%
See 1 more Smart Citation
“…In accordance with previous study (Hachfeld et al, 2015;Tatar et al, 2011) and our hypothesis, immigration-related self-efficacy was predicted by attitudes toward multiculturalism, such that a pluralistic multicultural attitude to school was related to higher immigration-related self-efficacy. Attitudes toward multiculturalism were not a significant predictor of teachers' diversity-related burnout, not in accordance with our hypothesis.…”
Section: Attitudes Toward Multiculturalismsupporting
confidence: 92%
“…Immigration-related self-efficacy. This section included nine statements based on the instrument developed by Tatar et al (2011), dealing with the teacher's relationship with immigrant students (e.g., "I believe that I am good at encouraging immigrant students to express their thought and feelings in class"). Respondents were asked to indicate the extent of their agreement with each statement on a 6-point scale ranging from 0 (never) to 5 (always).…”
Section: Questionnairesmentioning
confidence: 99%
“…Finally, in Study 2, only the ignoring differences ideology positively predicted cultural diversity-related stress. This finding is in line with other studies suggesting that the ignoring differences ideology is detrimental to psychological adjustment (Celeste et al 2019;Gutentag et al 2018;Tatar et al 2011). The ignoring differences ideology should be considered unrealistic and too cognitively demanding, and not a way to buffer possible concerns for teachers who are called to work with culturally and ethnically diverse students.…”
Section: Discussionsupporting
confidence: 90%
“…This is because the explicit and implicit devaluation of groups reaffirms the uneven distribution of resources, rights and privileges among the student population (Gomolla and Radtke 2009). Additionally, it has been found that teachers' cultural diversity beliefs in line with the ignoring differences ideology may be associated with higher levels of cultural diversity-related stress (Gutentag et al 2018;Tatar et al 2011). Notably, reporting a high level of cultural diversity-related stress is associated with high rates of leaving the teaching profession (Tatar and Horenczyk 2003).…”
Section: The Ignoring Differences Ideologymentioning
confidence: 99%
See 1 more Smart Citation